Qualitative Tests of Secondary Metabolite Compounds in Ethanol Extract of Spirulina platensis from Karimun Jawa Sea, Indonesia - Renni Yuniati; Muhammad Zainuri; Hermin Kusumaningrum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Spirulina platensis is a spiral green-blue algae that is abundant in the subtropical and tropical water bodies. S. platensis has several potentials to be used in the medical fields due to its wound healing and antitumor potentials. This research aimed to evaluate the secondary metabolite compounds contained in the ethanolic extract of S. platensis from Karimun Jawa Sea, Indonesia. The dried S. platensis was macerated and extracted using ethanol, then was filtered using Whatman filter paper. A series of tests has been done to determine the secondary metabolites in the ozonated oil using several chemistry tests and reagents in the ethanol extract of S. platensis. The tests found that S. platensis microalgae harvested from Karimun Jawa sea contains alkaloid, saponin, flavonoid, and quinone. As S. platensis from different region contains different substances, this research shows the substances contained in S. platensis from Karimun Jawa sea. With this research, we knew that S. platensis from Karimun Jawa islands contains alkaloid, saponin, flavonoid, and quinone which can be used as a medicinal ingredient.